2005
DOI: 10.1103/physrevd.72.084008
|View full text |Cite
|
Sign up to set email alerts
|

Separable sequences in Bianchi I loop quantum cosmology

Abstract: In this paper, we discuss the properties of one-parameter sequences that arise when solving the Hamiltonian constraint in Bianchi I loop quantum cosmology using a separation of variables method. In particular, we focus on finding an expression for the sequence for all real values of the parameter, and discuss the pre-classicality of this function. We find that the behavior of these preclassical sequences imply time asymmetry on either side of the classical singularity in Bianchi I cosmology.Comment: 5 pages, 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Many studies have already been devoted to Bianchi-I LQC [97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117]. In particular, it was shown that the bounce prediction is robust.…”
Section: Further Developmentsmentioning
confidence: 99%
“…Many studies have already been devoted to Bianchi-I LQC [97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117]. In particular, it was shown that the bounce prediction is robust.…”
Section: Further Developmentsmentioning
confidence: 99%
“…We can expand the function B(y) = β 0 + yF (y) in a Taylor series, to read off the values of the sequence β n for any real n, as done in previous work [14]. However, in this case the function is not easily written in a compact form.…”
Section: B βN Sequencementioning
confidence: 99%
“…Similar reasoning lets us ignore the difference between the full recursion relation and the "bulk" relation, where m ≥ 2 allows us to simplify the absolute value signs for m. 2 Notice that we are focussing solely on integer values of the parameter k, despite the fact that µ and τ (and hence m, n) can take any real value. It has been shown elsewhere [14] that using the sequence solution for integer values can be extended to all real numbers.…”
Section: B(y)mentioning
confidence: 99%
“…A crucial difference between this conserved quantity and the charge (15) obtained from the APS quantization is what happens to the prefactor of Q at the classical singularity. As stated above, for the APS model (13), at this singularity, C + (0) = 0, so Q can take any real value; this allows the charge for wave functions passing through the classical singularity to be non-zero, and thus provide a relation between semi-classical limits of the wave function far away from the v = 0 point. On the other hand, for the earlier quantization (22), we have the difference in volumes V µ+µ0 − V µ−µ0 at µ = 0 is V µ0 − V −µ0 = 0 so that the charge Q = 0 for any wave function passing through the µ = 0 classical singularity.…”
Section: Non-self-adjoint Constraint Equations In Lqcmentioning
confidence: 99%